ARCHITECTURAL DESIGN TOOLS FOR DEVELOPING STUDENT SPACE IMAGINATION IN TEACHING SCIENCES - Azamjon Komolkhanovich, Abdullaev (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article presents the tools and methods of intensive development of students' spatial imagination in the teaching of the subject of architectural design using computer technology and computer graphics.